22% Efficiency Inverted Perovskite Photovoltaic Cell Using Cation‐Doped Brookite TiO2 Top Buffer. Issue 16 (2nd July 2020) - Hu, Xiaowen; Liu, Chang; Zhang, Zhiyong; Jiang, Xiao‐Fang; Garcia, Juan; Sheehan, Colton; Shui, Lingling; Priya, Shashank; Zhou, Guofu; Zhang, Sen; Wang, Kai
Abstract: Simultaneously achieving high efficiency and high durability in perovskite solar cells is a critical step toward the commercialization of this technology. Inverted perovskite photovoltaic (IP‐PV) cells incorporating robust and low levelized‐cost‐of‐energy (LCOE) buffer layers are supposed to be a promising solution to this target. However, insufficient inventory of materials for back‐electrode buffers substantially limits the development of IP‐PV. Herein, a composite consisting of 1D cation‐doped TiO2 brookite nanorod (NR) embedded by 0D fullerene is investigated as a top modification buffer for IP‐PV. The cathode buffer is constructed by introducing fullerene to fill the interstitial space of the TiO2 NR matrix. Meanwhile, cations of transition metal Co or Fe are doped into the TiO2 NR to further tune the electronic property. Such a top buffer exhibits multifold advantages, including improved film uniformity, enhanced electron extraction and transfer ability, better energy level matching with perovskite, and stronger moisture resistance. Correspondingly, the resultant IP‐PV displays an efficiency exceeding 22% with a 22‐fold prolonged working lifetime. The strategy not only provides an essential addition to the material inventory for top electron buffers by introducing the 0D:1D composite concept, but also opens a new avenue to optimize perovskite PVs with desirable properties. Abstract : A composite consisting of 1D cation‐doped TiO2 brookite nanorod embedded by 0D fullerene is investigated as a top modification buffer for inverted perovskite photovoltaic (IP‐PV) cells. The resultant IP‐PV displays an efficiency exceeding 22% with a favorable stability. This work opens up more opportunities in expanding the material inventory for charge transfer layer in perovskite solar cells development and application.